Assessment of the contents related to screening on Portuguese language websites providing information on breast and prostate cancer - Daniel Ferreira; Helena Carreira; Susana Silva; Nuno Lunet (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The objective of this study was to assess the quality of the contents related to screening in a sample of websites providing information on breast and prostate cancer in the Portuguese language. The first 200 results of each cancer-specific Google search were considered. The accuracy of the screening contents was defined in accordance with the state of the art, and its readability was assessed. Most websites mentioned mammography as a method for breast cancer screening (80%), although only 28% referred to it as the only recommended method. Almost all websites mentioned PSA evaluation as a possible screening test, but correct information regarding its effectiveness was given in less than 10%. For both breast and prostate cancer screening contents, the potential for overdiagnosis and false positive results was seldom addressed, and the median readability index was approximately 70. There is ample margin for improving the quality of websites providing information on breast and prostate cancer in Portuguese.